Enhancing Creative Imagination Ability in Early Childhood: A Study on Differential Learning Assisted with Loose Parts Media and Social Skills - Purwati, Dwi; Astawan, I Gede; Antara, Putu Aditya (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Developing early childhood creative imagination skills in the learning process is very important. However, there are not many efforts to implement learning models that can support the development of students' creative imagination abilities. This study aims to analyze the effect of differentiated learning aided by loose parts media and social skills on creative imagination ability, as well as whether learning models and social skills interact with creative imagination ability. The method used in this research is a quasi-experiment with a post-test-only control group design. The data collection instrument for social skills and creative imagination ability used observation sheets with a scale of 1-4. Quantitative data obtained were analyzed with a two-way ANOVA. The results showed that differentiated learning assisted by loose parts media significantly affected creative imagination ability, while social skills had no significant effect. There is an interaction between differentiated learning models assisted by loose parts media and social skills on students' creative imagination ability. There was an increase in creative imagination ability in the group of students who follow differentiated learning aided by loose parts of media with high social skills.